If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2w + -1w) + -7 = 8w + 35 Combine like terms: 2w + -1w = 1w 2(1w) + -7 = 8w + 35 Remove parenthesis around (1w) 2 * 1w + -7 = 8w + 35 Multiply 2 * 1 2w + -7 = 8w + 35 Reorder the terms: -7 + 2w = 8w + 35 Reorder the terms: -7 + 2w = 35 + 8w Solving -7 + 2w = 35 + 8w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-8w' to each side of the equation. -7 + 2w + -8w = 35 + 8w + -8w Combine like terms: 2w + -8w = -6w -7 + -6w = 35 + 8w + -8w Combine like terms: 8w + -8w = 0 -7 + -6w = 35 + 0 -7 + -6w = 35 Add '7' to each side of the equation. -7 + 7 + -6w = 35 + 7 Combine like terms: -7 + 7 = 0 0 + -6w = 35 + 7 -6w = 35 + 7 Combine like terms: 35 + 7 = 42 -6w = 42 Divide each side by '-6'. w = -7 Simplifying w = -7
| 67+x=127x | | (D+1)=7 | | 11-3(x-1)=2(x+2) | | M+16=-9 | | 4d+7=39 | | 9x+1=4(10-x) | | 5g+1=7+2g | | 16-2x=1+x | | 3x-11+3x-11=2x-2 | | 6(2x-1)=18 | | -0.25y=-5 | | 12=2(k+1) | | 4+14x=4-6x | | 4(3m+5)-14=42 | | 28=3s-4b | | 4d-6d=-2 | | 7n/9-62=5n/9-48 | | 9y-4x=-16 | | 0.6(15+0.5)-0.9(25-1)= | | 69=60+9-2+3-1 | | 69=60+9-2+3 | | 3y+12=4y-2y+1 | | 12c-6=44 | | 69=60+8 | | .625m-.375=.5m+.875 | | x/3-2/9=4/9 | | 15n=290 | | -6m=-6m^2+5(-6m) | | x+3+2x-5=19 | | 17+3m=5m+9 | | y=3(4)*-1 | | x=180-(7x-12) |